Investigating Garment Drape Behaviour (Journal of Fiber Bioengineering and Informatics, 2015)
Drapeability is one of the most important visual properties affecting garment appearance. Even though\rthere are many studies concerned with fabric drape, understanding about the drape behaviour of\rgarments is very limited. This study analyzes the key properties affecting the drape behaviour of\rgarments to provide prediction equations. Results are statistically analyzed. From multiple regression\ranalysis, drape rank scores obtained from subjective analyses are predicted using weight, bending\rmodulus and extensibility measured at 100 gf/cm with a correlation coefficient of 0.94. Ranking values\robtained from subjective analyses can be more easily predicted using both circularity and wave length\rminimum. A new equation was derived to predict drape rank score values of garments (correlation\rcoefficient r = 0:97) depending on circularity and wavelength minimum.